An Air Quality Management System for Policy Support in Cyprus - Nicolas Moussiopoulos; Ioannis Douros; George Tsegas; Savvas Kleanthous; Eleftherios Chourdakis (Advances in Meteorology)
The recent air quality directive (2008/50/EC) encourages the introduction of modelling as a necessary tool for air quality assessment and management. Towards this aim, an air quality management system (AQMS) has been developed and installed in the Department of Labour Inspection (DLI) of the Republic of Cyprus. The AQMS comprises of two operational modules, providing hourly nowcasting and daily forecasting of the air quality status, implemented as an integrated model system that performs nested grid meteorological and photochemical simulations. A third operational module provides the capability of an interactive configuration of custom emission scenarios and corresponding model runs covering user-defined domains of interest. Statistical indicators are calculated at the end of each day for the measurement locations of DLI's air quality monitoring network. Besides, the system provides an advanced user interface, which is realised as a web-based application providing access to model results from any computer with an internet connection and a web browser.